Genetic derepression of a developmentally regulated lipopolysaccharide antigen from Rhizobium leguminosarum 3841. - Wood, E A (1989)
Monoclonal antibody AFRC MAC 203 recognizes a developmentally regulated lipopolysaccharide antigen in Rhizobium leguminosarum bv. viciae 3841. Transposon-induced mutants that constitutively expressed MAC 203 antigen were isolated. These strains were morphologically normal, showed no gross abnormalities in lipopolysaccharide size distribution on sodium dodecyl sulfate-polyacrylamide gels, and induced normal nitrogen-fixing nodules. However, the mutants lacked lipopolysaccharide epitopes recognized by another rat monoclonal antibody, AFRC MAC 281, suggesting that the corresponding epitopes may be interconverted or share a common precursor. In conjugational crosses, the transposon insertion associated with both the loss of MAC 281 antigen and the constitutive expression of MAC 203 antigen showed linkage to the chromosomal rif allele. A derivative of strain 3841 with a deletion spanning the nod-fix region of the symbiotic plasmid showed no altered expression pattern for MAC 203 antigen, suggesting that the relevant genetic determinants map to genomic sites that are not associated with nifA or any known genes on the symbiotic plasmid.